Associations between corrected serum calcium and phosphorus levels and outcome in dialysis patients in the Kumamoto Prefecture - Sueta, Daisuke; Tabata, Noriaki; Tanaka, Motoko; Hanatani, Shinsuke; Arima, Yuichiro; Sakamoto, Kenji; Yamamoto, Eiichiro; Izumiya, Yasuhiro; Kaikita, Koichi; Arizono, Kenji; Matsui, Kunihiko; Tsujita, Kenichi (Hemodialysis international, 2020)
Introduction Mortality in hemodialysis patients is relatively high; thus, its risk stratification is very important. There are insufficient data describing the current status of the management of serum phosphate and calcium levels. Methods We conducted a multicenter, prospective, registry study throughout the Kumamoto Prefecture in Japan. We enrolled 1993 patients at 58 facilities with complete explanatory data, including serum phosphate, corrected calcium, and intact parathyroid hormone levels. We categorized subjects into nine categories according to low, normal, and high levels of phosphate and corrected calcium levels. The endpoint was all‐cause mortality. Results Of the total number of subjects, 56.1% of the patients were in the normal phosphate and calcium category, and 72% and 77.1% had controlled serum phosphate and calcium levels, respectively. Two hundred twenty‐six deaths occurred during the follow‐up period. In the nine categories, the highest mortality rates were observed in the highest corrected calcium and lowest phosphate categories. Stepwise backward multivariate regression analyses identified the serum corrected calcium level (OR, 1.38; 95% CI, 1.06–1.79; P = 0.016) and the serum phosphate level (OR, 1.26; 95% CI, 1.08–1.48; P = 0.003) as significant and independent predictors of all‐cause mortality. Conclusions The corrected serum calcium and phosphate levels are associated with mortality in our dialysis population, with poorest survival in patients with high corrected serum calcium and low serum phosphorus.